Can justice and fairness enlarge international environmental agreements? - Christine Grüning; Wolfgang Peters (Games, 2010)
The literature on International Environmental Agreements (IEAs) predicts a rather low number of signatories to an IEA. This is in sharp contrast to empirical evidence. As experimental economics provides some evidence for more complex human behavior, extending the theory of IEAs to a broader class of preferences is clearly promising. The present paper shows that where countries' preferences incorporate justice and fairness there will be a strong incentive for them to choose similar abatement policies within and outside an IEA. Consequently, free-riding at the expense of the signatory states diminishes and participation in an IEA becomes a more successful strategy, so that the size of stable IEAs increases.
Keywords: 330; international environmental agreements; coalition formation; justice and fairness